2023
DOI: 10.1038/s41380-023-02001-6
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin blockade enhances motivational reward learning via enhancing striatal prediction error signaling and frontostriatal communication

Abstract: Adaptive human learning utilizes reward prediction errors (RPEs) that scale the differences between expected and actual outcomes to optimize future choices. Depression has been linked with biased RPE signaling and an exaggerated impact of negative outcomes on learning which may promote amotivation and anhedonia. The present proof-of-concept study combined computational modelling and multivariate decoding with neuroimaging to determine the in uence of the selective competitive angiotensin II type 1 receptor ant… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 68 publications
1
18
0
Order By: Relevance
“…This was also paralleled by the finding that such gene expressions were closely related to cognitive functions, such as inhibitory control and reward, at the core of symptomatic dysfunctions in ADHD. Intact inhibitory control and adaptive reward processing are intimately linked to (sub)cortical-cortical communication 73,74 and circuit level dysregulations in the underlying dysfunctionsDLPFC and basal ganglia pathways and their genetic modification have been reported in ADHD 75,76 . In addition, we also revealed metabolic dysfunctions of ADHD in oxygen (CMRO2) and glucose (CMRGlu).…”
Section: Gene-set Decoding Of Pls Componentsmentioning
confidence: 99%
“…This was also paralleled by the finding that such gene expressions were closely related to cognitive functions, such as inhibitory control and reward, at the core of symptomatic dysfunctions in ADHD. Intact inhibitory control and adaptive reward processing are intimately linked to (sub)cortical-cortical communication 73,74 and circuit level dysregulations in the underlying dysfunctionsDLPFC and basal ganglia pathways and their genetic modification have been reported in ADHD 75,76 . In addition, we also revealed metabolic dysfunctions of ADHD in oxygen (CMRO2) and glucose (CMRGlu).…”
Section: Gene-set Decoding Of Pls Componentsmentioning
confidence: 99%
“…78,79 Initial pharmaco-fMRI studies in humans furthermore indicate that an AT1R-blockade induced modulation of these circuits may mediate the regulatory role of the AT1R on reward, motivation and decision making in humans. 7,8 Network regulation of the AT1R and its association with dopaminergic, opioid and CRH systems Given that several of the complex effects of the AT1R may be mediated by interactions with other transmitter systems we modelled the spatiotemporal overlap of neurofunctional AT1R effects and receptor maps of selected candidate signaling systems. Our findings indicated that specifically the DRD5, OPRK1 and CRHR2 gene expression showed a distinct association with AT1R effects on brain regional FC such that DRD5 and OPRK1 interacted positively with AT1R blockade induced network level changes, while the CRHR2 exhibited a negative association with the pharmacological blockade effects.…”
Section: Target Engagement -Effects Of Acute At1r Blockade On Regiona...mentioning
confidence: 99%
“…1,3 Human pharmacological fMRI studies support the functional relevance of these circuits such that the blood-brain barrier permeable selective AT1R antagonist losartan: 1) attenuated amygdala threat reactivity, 21 2) facilitated regulation of threat via amygdala-hippocampal and amygdala-medial prefrontal pathways, 6,22,23 and 3) enhanced ventral striatal prediction errors and coupling in the mesocorticolimbic circuits during motivational paradigms. 7,8 Large population studies further indicate that (chronic) treatment with pharmacological AT1R blockers can reduce the incidence of PTSD symptoms. 10,24 While these results underscore a highly promising therapeutic potential of the AT1R, a recent multi-center randomized controlled clinical trial failed to determine treatment effects of an AT1R antagonist on PTSD symptomatology.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations